UPAYA MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR PKN POKOK BAHASAN GLOBALISASI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP TO GROUP EXCHANGE SISWA KELAS XII IPA 1 SMAN 3 KOTABUMI TAHUN PELAJARAN 2019--2020 - Agung Sulistiana (Eksponen, 2021)
This research was conducted at SMAN 3 Kotabumi with the aim of increasing activities and learning outcomes for Citizenship Education (Civics) subjects using a Cooperative learning model with the Group To Groupe Exchange type of Globalization material for students in grade 12 Science 1 SMA Negeri 3 Kotabumi, North Lampung Regency. 2019-2020. The type of research carried out is classroom action research where a treatment is carried out on the research subject, namely grade 12 IPA 1 SMAN 3 Kotabumi students for the 2019-2020 academic year. This research was conducted to examine the effect of the groupto-exchange learning model, which is one type of cooperative learning on the activities and learning outcomes of Citizenship Education (Civics) subjects for 12 Science 1 students on Globalization. In classroom action research, the term research cycle is known, in this study carried out as many as 2 cycles at the end of the cycle reflection is carried out to find out the shortcomings and weaknesses of its implementation as well as material to reduce errors that will occur in cycle 2. The results of each cycle obtained student learning outcomes data in the form of tests questions and results of observations of student activities in the form of activity observation sheets during research activities which were then analyzed data to find out the results of the research. Based on the results of observations and discussions, it was found that there was an increase in Civics learning outcomes for class 12 Science 1 students on Globalization material by 49.5% from cycle 1 to cycle 2. There was also an increase in student learning activities using the Group to group exchange type cooperative learning model on indicators discipline, cooperation, courtesy and tolerance during learning. Thus, it can be concluded that the use of the group to group exchange learning model in learning Civics subjects on globalization materials can improve learning activities and student learning outcomes of 12 Science 1 SMAN 3 Kotabumi for the 2019-2020 academic year.